(untitled) (AYUSHDHARA, 2023)
Diabetes mellitus is one of the most common non-communicable diseases in the world. Diabetes management in India confronts various obstacles, including increased incidence in urban and rural regions, a lack of disease awareness among the general public, inadequate health care facilities, high treatment costs, inefficient glycemic control, and an increase in the prevalence of diabetic complications. Diabetes insulin therapy is often administered via subcutaneous injections up to four times per day. Long-term insulin therapy, along with the intrusive aspect of its administration, has resulted in issues with patient compliance, impacting patient outcomes. Diabetes is a chronic condition that arises when the pancreas does not create enough insulin or when the body cannot adequately use the insulin that is produced. Insulin is a hormone that regulates blood glucose levels. Ayurvedic preventive practises can help to keep the disease at bay. Sedentary lifestyle and eating habits are thought to be the primary causes. It is characterised in Ayurveda as Vataja pramehas, which can be managed conservatively with exercise, nutrition, and internal treatment.